(untitled) (Bioagro, 2020)
One of the most important properties of many fruits is their antioxidant activity, which depends on the species, part of the fruit and their origen. The objective of the research was to determine the content of phenolic compounds and antioxidant capacity of guava (Psidium guajava), blueberry (Vaccinium myrtillus), pitahaya (Selenicereus megalanthus) and aguaymanto (Physalis peruviana) from different origins. Ethanolic extracts were obtained from the different samples and phenolic compound contents and antioxidant activity was determined. Total phenols were determined using the Folin Ciocalteu technique, and antioxidant activity by the technique of capturing free radicals (DPPH). Blueberry was the species with the highest antioxidant activity, which varied slightly according to their origin. Guava ranked second, and both fruits also presented higher phenolic content. The calyx of aguaymanto contains significant amounts of phenolic compounds although not very high antioxidant activity. The antioxidant capacity of the Peruvian blueberry was moderately higher than that of United States, and the capacity of the Peruvian guava was slightly lower than that of Brazilian guava. The fruits of pitahaya and aguaymanto, from any origin, showed very little antioxidant activity.